Ethnoparenting: Pengenalan Bahasa Krama Inggil Sejak Dini dalam Lingkungan Keluarga Komunitas Kejawen Kalitanjung - Zubaedah, Siti; Hafidz, Nur; Wulandari, Suci (Generasi Emas, 2023)
this research will discuss how to introduce the Krama Inggil language from an early age in the family environment in the Kejawen Kalitanjung Community in Tambaknegara Village, Rawalo District, Banyumas Regency. The subjects of this study were five families in the Kejawen Kalitanjung Community. This research method uses field qualitative methods (field research) through data collection techniques by conducting observations, interviews, and documentation. Informants in the study were traditional leaders, parents and children. Results of the study prove that the introduction of the Krama Inggil language from an early age in the family environment of the Kejawen Kalitanjung Community uses four methods of language recognition, namely; (1) introduction to the Krama Inggil language through parental experiences, (2) introduction to the Krama Inggil language through storytelling media, (3) introduction to the Krama Inggil language through surrounding objects, (4) introduction to the Krama Inggil language through interaction and communication. These four habits are carried out by families in the Kejawen Kalitanjung Community in instilling attitudes, actions, and words from ancestors who adhere to Javanese cultural traditions. Implication is that children are able to gain good Javanese language tools, communicate politely and politely, develop a sense of sympathy, and have Javanese nobility skills.